Web 2.0 and Higher Education: Exploring Emerging Trends in Digital Teaching and Learn-ing - Rajkumar Rajkumar; Tertu Shiweda; Manuela Dan (PT. Sinergi Bersahaja Sejahtera, 2026)
Background. The rapid expansion of internet technologies has significantly transformed university education, reshaping how knowledge is created, shared, and experienced. The emergence of Web 2.0 innovations has introduced interactive, collaborative, and user-generated approaches that challenge traditional pedagogical models and redefine the dynamics of teaching and learning in higher education. Purpose. This paper aims to provide a comprehensive overview of the role of the Internet, particularly Web 2.0 technologies, in transforming university education, with a focus on emerging trends in teaching strategies, student engagement, and participatory learning environments. Method. This study adopts a qualitative review approach, synthesizing relevant literature on Web 2.0 technologies in higher education. The analysis focuses on key digital tools such as blogs, wikis, social media platforms, and online learning communities, examining their pedagogical implications and contributions to evolving instructional practices. Results. The review reveals that Web 2.0 technologies significantly reshape traditional pedagogy by fostering interactive and collaborative learning environments. These technologies enhance student engagement, promote active participation, and support knowledge co-construction through user-generated content. Furthermore, they enable more flexible and student-centered learning approaches, encouraging autonomy, creativity, and continuous interaction beyond the classroom. Conclusion. The integration of Web 2.0 technologies plays a crucial role in advancing university education in the digital age. These innovations contribute to the development of more participatory and dynamic learning ecosystems that align with contemporary educational needs. Higher education institutions are encouraged to strategically adopt and integrate Web 2.0 tools to enhance teaching effectiveness and optimize student learning experiences.